Tratamiento de cicatrices de acné con el uso de ácido salicilico y micropunción en paciente masculino de 19 años - Oyasa Salan, Ana Del Rocío (2025)
This study aims to evaluate the efficacy of the combined treatment of 10% salicylic acid pH 3.5 and microneedling in improving acne scars in a 19-year-old male patient. Salicylic acid is a beta-hydroxy acid (BHA) with exfoliating, keratolytic, and anti- inflammatory properties, that facilitate the removal of dead cells, unclog pores, and reduce inflammation. It prevents the formation of new lesions and promotes cell renewal. Microneedling is a minimally invasive procedure that uses a device with fine needles to create microchannels in the skin. This process stimulates the production of collagen and elastin, which are essential for skin regeneration. Eight sessions are performed. The frequency and number of sessions depend on the scars' severity and the patient's individual response. Results: The combination of salicylic acid and microneedling has proven effective in improving acne scars. Salicylic acid works in preventing new lesions and exfoliating the skin, while microneedling contributes to the reduction of existing scars by stimul ating tissue regeneration. Conclusions: The combined treatment of salicylic acid and microneedling offers a comprehensive approach to managing acne scars. The proposed protocol is multifaceted, providing significant and safe results in improving the texture and appearance of the skin, making it an effective option for patients with acne scars.